2018
DOI: 10.1088/1681-7575/aaa368
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating gold nanorod samples using particle size and shape distributions from transmission electron microscope images

Abstract: Size and shape distributions of gold nanorod samples are critical to their physico-chemical properties, especially their longitudinal surface plasmon resonance. This interlaboratory comparison study developed methods for measuring and evaluating size and shape distributions for gold nanorod samples using transmission electron microscopy (TEM) images. The objective was to determine whether two different samples, which had different performance attributes in their application, were different with respect to thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…After seven weeks of dissolution, there are no particles with areas greater than 20 nm 2 , no apparent bimodal appearance to the area distribution, and an expanded aspect ratio range, 0.50 to 0.98. Bivariate analysis 56 of the two datasets also confirms that they are different statistically. The p-values between the two plots were much less than 0.05.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…After seven weeks of dissolution, there are no particles with areas greater than 20 nm 2 , no apparent bimodal appearance to the area distribution, and an expanded aspect ratio range, 0.50 to 0.98. Bivariate analysis 56 of the two datasets also confirms that they are different statistically. The p-values between the two plots were much less than 0.05.…”
Section: Resultsmentioning
confidence: 56%
“…Nanoceria size and shape distributions were obtained by acquiring TEM images of cassette dispersions 66 , using automated methods for particle capture 57 (ImageJ), comparing distribution statistics, fitting the parameters of reference distribution models 66 , and evaluating bivariate correlations 56 . These are programmed in R and have been implemented in a series of ShinyApp™ tools that are available on the web 67 .…”
Section: Materials and Experimental Methodsmentioning
confidence: 99%
“…The quantitative analysis of micrographs displaying enough particles provides the distribution of the nanorod dimensions. Yet, unbiased and reproducible analysis of the micrographs is not an easy task as Grulke et al showed in their work where they propose a standardized protocol to analyze such images [ 107 ].…”
Section: Methods Of Characterizationmentioning
confidence: 99%
“…Many of the detailed studies on physical chemical properties of nanomaterials have focused on certified reference materials and representative test materials, such as those available as part of the European Commission Joint Research Centre Nanomaterial Repository. These studies provide important information on the level of agreement between laboratories and methods for standard materials, which are typically spherical, monodisperse and readily dispersible (for example, polystyrene, silica and gold nanoparticles) [5][6][7]. A recent study has aimed to address batch-to-batch variability in nanomaterials by synthesizing multiple batches of four different nanomaterials in different laboratories using several synthetic methods [8].…”
Section: Introductionmentioning
confidence: 99%